Hybrid localization techniques for GSM-WCDMA cellular radio system / Ukasyah Mahamod - Mahamod, Ukasyah (2013)
The communication industry have seen a big growth with the telecomunication system itself has evolve from the fixed network to wireless network. The system improvement took place very fast to support demand of users in term of higher throughput and data rates besides to support new services that needs device location information. Mobile devices today has become a very power tool and with the wireless connectivity becoming much more readily available the user of mobile devices as rapidly increase. With the increase of user we are seeing growing demand of information and application moving around the network. Location Based Services (LBS) is an important features in the cellular radio network such as Global System for Mobile Communications (GSM), Wideband Code Division Multiple Access (WCDMA) and Long Term Evolution (LTE). There are several mobile station positioning determination techniques for LBS such as Cell-Identification (Cell-ID), Angle of Arrival (AOA), Time of Arrival (TOA), Observed-Time Difference of Arrival (OTDOA), Enhanced-Observed Time Difference of Arrival (E-OTD) and Global Positioning Services (GPS). The accuracy of positioning or localization in such single layer network depend on the Location Determination Technique or Technology (LDT) implemented; the Enhanced Observed Time Difference (E-OTD) in GSM and Observed Time Difference Of Arrival (OTDOA) for WCDMA but subjected to signal hearability from at least three Base Station (BSs) or NodeBs. This paper present hybrid localization techniques for a multilayer or heterogeneous GSM WCDMA network when a single layer network experience low signal hearability. This can be resolve by gathering at least three signal hearability from multilayer network infrastructure or using previous location information to reduce LDT error. The proposed method has been implemented and evaluated using simulation under various mobility models. Simulation model for the OTDOA, E-OTD and Hybrid techniques was created using MATLAB 7.0 during the work of this dissertation. Simulation shown that the LDT error for hybrid technique can been improved as compared to E-OTD and OTDOA and met E911 requirement.